Simultaneous Estimation of Salbutamol, Oxtriphylline and Bromhexine Hydrochloride in Tablet Dosage Form by RP-HPLC - Chakravarthi, K.S.; Devanna, N. (Asian Journal of Chemistry, 2017)
A simple, rapid, accurate, specific and stability indicating reverse phase HPLC method has been developed and validated for the simultaneous estimation of salbutamol, oxtriphylline and bromhexine hydrochloride in bulk drug and pharmaceutical tablet dosage form. The chromatographic separation was performed on the kromasil C18 column (250 mm × 4.6 mm, 5 μm particle size), using a mobile phase of orthophosphoric acid buffer:acetonitrile (65:35 v/v), at a flow rate of 1.0 mL/min at an ambient temperature of 25 °C with the detection wavelength at 260 nm. The retention times of salbutamol, oxtriphylline and bromhexine hydrochloride was found to be 2.03, 2.90 and 4.92 min, respectively. The proposed method has been validated for linearity, range, precision, accuracy and robustness were within the acceptance limit according to ICH Q2R1 guidelines. Quantification of the components in actual tablet formulations was calculated against the responses of freshly prepared external standard solutions. In the linearity test correlation coefficient was found to be 0.999 for all the molecules, percentage relative standard deviation (RSD) results from precision studies were 0.7, 0.2 and 0.3; mean percentage recoveries in accuracy studies were found to be 99.33, 99.44 and 99.36 % for salbutamol, oxtriphylline and bromhexine hydrochloride, respectively. Very low concentrations of LOD and LOQ indicate the method was highly sensitive enough. The designed validated method can be used effectively in the laboratory for regular determination of salbutamol, oxtriphylline and bromhexine hydrochloride in tablet formulation and bulk form.